Pengaruh Inklusi Keuangan, Penggunaan Informasi Akuntansi, dan Karakteristik Wirausaha terhadap Keberhasilan UMKM di Kecamatan Buleleng pada Masa Pandemi Covid-19 - sukmayanti, leny; Devi, Sunitha (Universitas Pendidikan Ganesha, 2021)
This quantitative approach research aims to determine the influence of financial inclusion, the use of accounting information, and entrepreneurial characteristics on the success of MSMEs in Buleleng Sub-district during the Covid-19 pandemic. Sample size is determined by using slovin formula, so that 85 MSMEs are obtained by selecting respondents using purposive sampling. The data sources in this study are primary and secondary data. The method of data collection is carried out by the dissemination of questionnaires. The data analysis method used is multiple linear regression tests. The data was analyzed using SPSS version 23 for windows. The results of this study show that: (1) financial inclusion has a positive and significant effect on the success of MSMEs in Buleleng Sub-district during the covid-19 pandemic; (2) the use of accounting information has a positive and significant effect on the success of MSMEs in Buleleng Sub-district during the covid-19 pandemic; and entrepreneurial characteristics have a positive and significant effect on the success of MSMEs in Buleleng sub-district during the covid-19 pandemic. Â